Development and effectiveness of a 7Es-based interactive science pocket for grade 6 digestive system learning - Af-Ida S. Saipoden; Sittie Haifah M. Pascan; Monera A. Salic-Hairulla; Vanjoreeh A. Madale; Christine Mae B. Tecson (Journal of Education and Learning (EduLearn), 2026)
Despite the availability of various instructional resources, teaching abstract biological concepts like the human digestive system remains a challenge for elementary learners due to their developmental stage and the limitations of traditional textbooks. In response, this study aimed to develop and validate the 7Es Learning Pocket (LeaP), an innovative, portable instructional material anchored in the constructivist approach and structured around the 7Es instructional model—elicit, engage, explore, explain, elaborate, evaluate, and extend. The study adopted the 4D model (define, design, develop, and disseminate) and engaged 42 grade 6 students from a public elementary school, along with expert science teachers for validation. During the development phase, qualitative feedback from learners and expert validators guided iterative refinements of the LeaP, with experts rating it “very satisfactory” in content, format, organization, and information accuracy. Quantitative evaluation included paired samples t-test comparing pretest and posttest scores of 42 learners, revealing significant improvement from a mean of 7.12 to 16.79 (t=18.36, p0.001). Additionally, 81-90% of learners demonstrated “very satisfactory” procedural knowledge across all 7Es activities. Learner perception data further affirmed high satisfaction, engagement, and perceived usefulness of the material. These findings confirm that the 7Es LeaP is a well-validated and effective instructional tool that enhances conceptual understanding and promotes active learning in elementary science education.